Gastrointestinal Stromal Tumor (GIST) - Ali Ramzi (Journal of Social Science, 2023)
Gastrointestinal stromal tumor (GIST) are the most common mesenchymal tumor of the gastrointestinal tract and most common malignancy of the small intestine. Although the exact prevalence of GIST is not known, GIST was recognized as tumor it's arise from interstitial cells of Cajal. Most of the GISTs driven by a KIT or platelet-derived growth factor receptor alpha (PDGFRA) mutation. Histologically, GISTs look like spindle cell tumors most of the time, but they can be epitheoid or mixed type. Clinically, patients with small GISTs remain asymptomatic. In another case, patients with larger GISTs present with various symptoms depending on the location of the GISTs. Most of GISTs are located in the stomach or small bowel. But, they can involve almost any segment of the gastrointestinal tract from distal esophagus to anus. Diagnosis is suspected on imaging and endoscopic studies, and confirmed by tissue acquisition with immunohistochemical staining. The various endoscopic modalities of resection are increasingly tried. Surgical resection is the treatment of choice. In management of larger GISTs, tyrosine kinase inhibitors are extremly useful. Treatment options for metastatic GISTs also include radiotherapy, chemotherapy, hepatic artery embolization, chemoembolization, and radiofrequency ablation.